2020
DOI: 10.3390/pharmaceutics12030211
|View full text |Cite
|
Sign up to set email alerts
|

Mucoadhesive Budesonide Formulation for the Treatment of Eosinophilic Esophagitis

Abstract: Eosinophilic esophagitis (EE) is a chronic immune/antigen-mediated esophageal inflammatory disease for which off-label topical corticosteroids (e.g., budesonide) are widely used in clinic. In general, thickening excipients are mixed with industrial products to improve the residence time of the drug on the esophageal mucosa. The compounding procedures are empirical and the composition is not supported by real physicochemical and technological characterization. The current study aimed to propose a standardized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Last but not least, the article that does not deal with dermal application describes a ''Mucoadhesive Budesonide Formulation for the Treatment of Eosinophilic Esophagitis (EE)" [12]. The authors present results from a study that revealed a standardized budesonide oral formulation intended to improve the resistance time of the drug on the esophageal mucosa for EE treatment.…”
mentioning
confidence: 99%
“…Last but not least, the article that does not deal with dermal application describes a ''Mucoadhesive Budesonide Formulation for the Treatment of Eosinophilic Esophagitis (EE)" [12]. The authors present results from a study that revealed a standardized budesonide oral formulation intended to improve the resistance time of the drug on the esophageal mucosa for EE treatment.…”
mentioning
confidence: 99%
“…In their article, Casiraghi, A. et al claim that [ 1 ] “the compounding procedures (in order to compound oral viscous budesonide-author’s addition) are empirical and the composition is not supported by real physicochemical and technological characterization”. Indeed, Casiraghi et al analyzed a few relevant aspects of the formulation of oral viscous budesonide in their article, such as rheological properties, syringeability, mucoadhesiveness, and in vitro penetration of budesonide in porcine esophageal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A key consideration in therapy with topical corticosteroids is the time that the drug remains in contact with the mucosa, as this duration is directly associated with histological improvement [ 46 ]. Therefore, various modifications of compounded OVB have been developed to improve the local effects of steroid delivery, and these have been subjected to randomised placebo-controlled trials [ 78 , 79 , 80 ].…”
Section: Emerging Delivery Methodsmentioning
confidence: 99%